2013
DOI: 10.1016/j.ijggc.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Geological storage of CO2: Application, feasibility and efficiency of global sensitivity analysis and risk assessment using the arbitrary polynomial chaos

Abstract: With them the seed of Wisdom did I sow, And with mine own hand wrought to make it grow; And this was all the Harvest that I reap'd-"I came like Water, and like Wind I go."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…In general, CO 2 -EOR uncertainty sources may be classified as geological, physical and operational (Ashraf et al, 2013;Yang et al, 2014). Geological uncertainties associated with heterogeneity have attracted significant attention in recent years, with many studies suggesting heterogeneity as the primary source of uncertainty in model forecasts of CO 2 storage capacity, CO 2 plume extent, CO 2 migration and storage performance, and CO 2 leakage (Deng et al, 2012;Li and Zhang, 2014;Tian et al, 2014;Dai et al, 2014a;Liu and Zhang, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, CO 2 -EOR uncertainty sources may be classified as geological, physical and operational (Ashraf et al, 2013;Yang et al, 2014). Geological uncertainties associated with heterogeneity have attracted significant attention in recent years, with many studies suggesting heterogeneity as the primary source of uncertainty in model forecasts of CO 2 storage capacity, CO 2 plume extent, CO 2 migration and storage performance, and CO 2 leakage (Deng et al, 2012;Li and Zhang, 2014;Tian et al, 2014;Dai et al, 2014a;Liu and Zhang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, typical Monte Carlo methods are computationally expensive as they require a large number of model simulations. Recently, several studies applied polynomial chaos expansion (PCE) to quantify risks of geological CO 2 storage (GCS) (Zhang and Sahinidis, 2013;Oladyshkin et al, 2010Oladyshkin et al, , 2011Ashraf et al, 2013). The PCE approach was first introduced by Wiener (1938) to determine the evolution of uncertainty in dynamic systems based on homogenous chaos theory.…”
Section: Introductionmentioning
confidence: 99%
“…evolutionary algorithms, machine learning and particle swarms) are continuously adapted to reservoir simulation, and industry workflows for uncertainty quantification have been updated accordingly (e.g. Hajizadeh et al 2011;Abdollazadeh et al 2013;Arnold et al 2013;Ashraf et al 2013;Dehdari et al 2013;He & Durlofsky 2013;Park et al 2013;Peters et al 2013;El-Sheikh et al 2014). However, it is not clear how readily those new algorithms, which are commonly developed for well-known and sometimes slightly idealized benchmark problems comprising clastic reservoir models, can be applied to carbonate reservoirs.…”
Section: Background and Challengesmentioning
confidence: 99%
“…Oladyshkin and Nowak observed that as every set of random data, as well as a continuous or discrete PDF, can be described using the moments without making any assumptions about the shape or existence of a suitable probability distribution, the moments provided a very general approach to propagate data without requiring the determination of deterministic PDFs. Oladyshkin and Nowak [7] promoted this concept in the geo-sciences by successfully applying it to identify uncertainties in carbon dioxide storage in geological formations [15,16,17] and also for robust design [18]. Moreover, Oladyshkin and Nowak presented a derivation of the optimal orthogonal polynomials from the moments.…”
Section: Introductionmentioning
confidence: 99%